Research and simulation analysis of Jack based dental treatment chair human–machine system - Xiaoxiao Xie; Yuxin Liu; Jun Li; Yu Zhang (Scientific Reports)
Abstract With the continuous changes in people’s dietary habits, oral health issues have become a growing concern. As an essential device in the dental treatment process, the rationality and comfort of dental treatment chairs have become a focal point for patients during treatment. To enhance both comfort and efficiency for dental patients, an analysis of patient behavior and posture was conducted in the treatment environment. Jack simulation software was employed to perform ergonomic analysis on various factors, including the visual field, comfort, lower back stress, and static strength of dental patients within a simulated environment. Based on the analysis results, improvements were made to the design of the dental treatment chair, leading to the development of an enhanced plan. Simulation analysis of the revised plan indicated that patient comfort was significantly improved, the treatment process became more convenient, and the overall efficiency of dental treatment, along with patient comfort, was effectively enhanced.